Management of seborrhoeic keratosis and actinic keratosis with an erbium:YAG laser—experience with 547 patients. Issue 7 (July 2019) - Sayan, A.; Sindel, A.; Ethunandan, M.; Ilankovan, V.
Abstract: Seborrhoeic keratosis and actinic keratosis are common skin lesions, and the latter is a precursor for skin malignancy. The treatment regime can be lesion-directed or field-directed. Current lesion-directed treatments include cryotherapy, shave excision, and laser ablation. Field-directed treatment typically encompasses multiple topical agents. This article presents the authors' experience of lesion- and field-directed erbium:YAG laser treatment of 547 patients (Fotona Dualis XS Laser). In this series of patients, those who had resurfacing as field therapy showed no recurrence during the 12-month review period. However, there were six cases of recurrence in the group who underwent lesion-directed treatment over the same period. Furthermore, the results illustrated that the incidence of recurrence of actinic keratosis with malignant transformation was around 2.5%. The production of p53-negative keratin sites after laser ablation acts as a protective environment in the prevention of cutaneous malignancies. Thus, laser ablation not only removes lesions and resurfaces, but also protects against skin cancer. Therefore, this treatment is very welcome, especially in light of the increasing incidence of skin cancers.